Stock Market Response to Unexpected Dividend Changed in Indonesia - Daniel Wahap; Michael Basrie; Vina Nugroho (Universitas Pelita Harapan, 2022)
The writer finds that bond rating and dividend can change the firm value. Specifically, when a firm with bond rating has an increase in their dividend, their firm value will decrease. While when the firm without bond rating has an increase in their dividend, their firm value will also increase. It is very strange as to why the firm with bond rating can decrease in their firm value when their dividend is increasing. In this research, the writer explains this phenomena. Besides explaining this phenomena, the writer also can prove that bond rating and dividend is really critical in determining the firm value by conducting two researches (firm with and without bond rating) which other researchers have not done yet. The data that will be using is the firms with and without bond rating in Indonesia between 2007 and 2016.